The Effectiveness of the BAHAGIA Package on the Subjective Well-Being of Post-Stroke Patients - Melsandi Melsandi; M Sobirin Mohtar; Asmadiannor Asmadiannor (Poltekkes Kemenkes Semarang, 2023)
Background: stroke can leave symptoms or further impacts in all aspects of life such as loss of doing activities and changing roles. Changes that occur in post-stroke patients need to be given home care therapy, one of which is using the